Lithium battery positive electrode slurry composite additive and use method thereof
By using specific composite additives and stirring devices in the slurry of the lithium battery positive material, the problem of difficulty decentralizing the lithium iron phosphate positive pole material in the preparation of the slurry is solved, and the more efficient uniform pulp and more stable polar sheet performance are achieved Essence
Patent Information
- Application Number
- CN202411739517.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-24
AI Technical Summary
Lithium iron phosphate positive electrode material is difficult to disperse during the slurry preparation process, resulting in particle agglomeration and affecting battery performance. Traditional methods such as extending homogenization time increase cost and time, and the adhesion performance decreases under the proportion of high active substances, resulting in the electrode Film defect.
A composite additive of a lithium battery positive slurry, including hexaf methane triaxyne, oleic acid, polyoxide alkylin phenol, and N-methylpidopiol. Diversion and bonding performance.
It effectively avoids particle agglomeration, shortens the homogenization time, improves the bonding ability of the slurry, enhances the stability of the pole piece, and avoids the occurrence of pole piece defects.
Smart Images

Figure CN119361711A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a composite additive for lithium battery positive electrode slurry and a use method thereof. Background Art
[0002] Lithium-ion batteries have become the first choice in the field of energy storage due to their high energy density and long cycle life. In the composition of lithium-ion batteries, positive electrode materials play a vital role. Lithium iron phosphate, as a common positive electrode material, has the advantages of low cost, high safety, and good cycle performance. However, it also has some problems that cannot be ignored: due to the small particle size of lithium iron phosphate, its specific surface area is large, and the interaction force between particles is strong, which makes it difficult to disperse during the slurry preparation process and easily causes particle agglomeration; particle agglomeration will cause scratches in the subsequent coating process, resulting in electrode defects, which seriously affects the performance of the battery.
[0003] At present, the industry often adopts the method of extending the homogenization time to reduce particle agglomeration. By extending the stirring time, the particles can be more fully dispersed in the slurry, thereby improving the performance and consistency of the battery. However, simply extending the homogenization time means that more manpower and time costs are required, which increases the company's operating costs and reduces production capacity. In the case of growing market demand, it may affect the product supply speed and the company's competitiveness. In addition, the conditions for the homogenization and storage process of the positive electrode material are very harsh. The introduction of moisture in this process will cause the slurry to gel, resulting in slurry failure.
[0004] At the same time, in order to make lithium-ion batteries have a higher energy density, the industry generally chooses to increase the proportion of active materials and reduce the binder during the homogenization process. Due to the reduction of binders, the surface coating is prone to cracking and falling off during the coating and drying process, causing pole defects. Based on the background technology, lithium iron phosphate materials are prone to particle agglomeration during the homogenization process, and the slurry bonding performance is reduced at a high proportion of active substances, causing pole defects. The patent of the present invention provides a positive electrode additive and a method of using it to solve the above problems. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A composite additive for lithium battery positive electrode slurry, comprising the following raw materials in mass fraction: 15%-30% hexamethylcyclotrisiloxane, 15%-30% oleic acid, 5%-15% polyoxyethylene alkylphenol ether and 25%-65% N-methylpyrrolidone.
[0007] The present invention also provides a method for using a composite additive for a lithium battery positive electrode slurry, comprising the following steps:
[0008] Active material: conductive carbon: polyvinylidene fluoride: composite additive are mixed in a ratio of 97:2:0.8:0.2; the mixture is stirred into a slurry using a stirring device, and then coated.
[0009] Preferably, the active material is lithium iron phosphate.
[0010] The composite additives need to be added according to the actual solid content of the composite additives, and then about 35% of N-methylpyrrolidone is added according to the target slurry solid content of 65%.
[0011] Preferably, a composite additive for positive electrode slurry of a lithium battery comprises the following raw materials in mass fractions: 20% hexamethylcyclotrisiloxane, 20% oleic acid, 10% polyoxyethylene alkylphenol ether and 50% N-methylpyrrolidone.
[0012] Preferably, the stirring device includes a tank body provided with an inlet pipe and an outlet pipe, a cover plate is provided at the upper end of the tank body, a motor is installed above the cover plate, a stirring assembly and a material mixing assembly are provided below the cover plate, and the motor drives the stirring assembly and the material mixing assembly to reciprocate to stir and homogenize the mixture.
[0013] Preferably, the stirring assembly comprises a rotating shaft connected to the output shaft of the motor, a connecting piece is outer-circuited by the rotating shaft, and stirring plates are installed on both sides of the connecting piece.
[0014] Preferably, the material leveling assembly includes a gear sleeved on the outside of the rotating shaft and two symmetrically arranged racks, the gear is meshed with the rack, a connecting rod is installed on the outside of the rack, a material leveling plate is provided at the lower end of the connecting rod, a through hole is opened on the material leveling plate, the rack slides in two structurally symmetrical limit blocks, and the limit blocks are fixedly connected to the lower end of the cover plate.
[0015] Beneficial effects of the present invention:
[0016] 1. Improve the dispersion effect during the homogenization process of the positive electrode material, achieve the dispersion of agglomerated particles, and effectively avoid secondary agglomeration during the homogenization process;
[0017] 2. Shorten the homogenization time, improve the homogenization efficiency, and increase the equipment capacity;
[0018] 3. Enhance the bonding ability of the slurry, improve the peeling strength between the slurry and the current collector, and avoid electrode sheet defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the homogenous coating photo structure of Examples 1-4 of the present invention.
[0020] Figure 2 It is a schematic diagram of the homogenous coating photo structure of comparative examples 1-4 of the present invention.
[0021] Figure 3 Schematic diagram of slurry stability evaluation of Examples 1-4 of the present invention.
[0022] Figure 4 Schematic diagram of slurry stability evaluation of comparative examples 1-4 of the present invention.
[0023] Figure 5 It is a schematic structural diagram of the stirring device of the present invention.
[0024] Figure 6 It is a connection diagram of the stirring component and the material mixing component in the present invention.
[0025] Among them, 1-tank body, 2-cover plate, 3-motor, 4-stirring assembly, 5-mixing assembly, 6-rotating shaft, 7-connecting piece, 8-stirring plate, 9-gear, 10-rack, 11-connecting rod, 12-mixing plate, 13-through hole, 14-limiting block. DETAILED DESCRIPTION
[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0027] like Figures 1 to 6 As shown, a composite additive for lithium battery positive electrode slurry includes the following raw materials in mass fractions: 15%-30% hexamethylcyclotrisiloxane, 15%-30% oleic acid, 5%-15% polyoxyethylene alkylphenol ether and 25%-65% N-methylpyrrolidone.
[0028] The present invention also provides a method for using a composite additive for a lithium battery positive electrode slurry, comprising the following steps:
[0029] Active material: conductive carbon: polyvinylidene fluoride: composite additive are mixed in a ratio of 97:2:0.8:0.2; the mixture is stirred into a slurry using a stirring device, and then coated.
[0030] The active material is lithium iron phosphate.
[0031] The composite additives need to be added according to the actual solid content of the composite additives, and then about 35% of N-methylpyrrolidone is added according to the target slurry solid content of 65%.
[0032] The present invention provides a composite additive for positive electrode slurry of lithium battery, comprising the following raw materials in mass fractions: 20% hexamethylcyclotrisiloxane, 20% oleic acid, 10% polyoxyethylene alkylphenol ether and 50% N-methylpyrrolidone.
[0033] The stirring device comprises a tank body 1 provided with an inlet pipe and an outlet pipe, the outlet pipe may be provided with a valve, a cover plate 2 is provided at the upper end of the tank body 1, a motor 3 is installed above the cover plate 2, a stirring assembly 4 and a material mixing assembly 5 are provided below the cover plate 2, the motor 3 drives the stirring assembly 4 and the material mixing assembly 5 to reciprocate to stir and homogenize the mixture. The stirring assembly 4 comprises a rotating shaft 6 connected to the output shaft of the motor 3, the rotating shaft 6 is outer-engaged with a connecting member 7, and stirring plates 8 are installed on both sides of the connecting member 7. The material mixing assembly 5 comprises a gear 9 sleeved on the outside of the rotating shaft 6 and two symmetrically arranged racks 10, the gear 9 meshes with the rack 10, a connecting rod 11 is installed on the outer side of the rack 10, a material mixing plate 12 is provided at the lower end of the connecting rod 11, a through hole 13 is opened on the material mixing plate 12 to reduce the liquid flow impact on the material mixing plate 12, and the rack 10 slides in two symmetrically structured limit blocks 14, and the limit blocks 14 are fixedly connected to the lower end of the cover plate 2.
[0034] The compound is added through the inlet pipe of the stirring device, and the material is discharged through the outlet pipe after the stirring is completed. The forward and reverse rotation of the motor 3 is started to drive the rotation of the shaft 6 and the gear 9, so that the stirring plate 8 stirs the compound clockwise or counterclockwise to improve the stirring uniformity. At the same time, due to the rotation of the gear 9, the rack 10 meshing with it slides in two structurally symmetrical limit blocks 14, driving the material leveling plate 12 to move, and the compound is rowed, thereby improving the stirring and leveling efficiency and reducing the situation where the compound sticks and is difficult to stir evenly.
[0035] Example 1: Composite additive [hexamethylcyclotrisiloxane 20% + oleic acid 20% + polyoxyethylene alkylphenol ether 10% + N-methylpyrrolidone 50%]
[0036] 1. Prepare the composite additive according to [hexamethylcyclotrisiloxane 20% + oleic acid 20% + polyoxyethylene alkylphenol ether 10% + N-methylpyrrolidone 50%];
[0037] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0038] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0039] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode.
[0040] Example 2: Composite additive [octamethylcyclotetrasiloxane 20% + oleic acid 20% + polyoxyethylene alkylphenol ether 10% + N-methylpyrrolidone 50%]
[0041] 1. Use octamethylcyclotetrasiloxane instead of hexamethylcyclotrisiloxane as the composite additive component;
[0042] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0043] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0044] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode;
[0045] Example 3: Composite additive [hexamethylcyclotrisiloxane 20% + citric acid 20% + polyoxyethylene alkylphenol ether 10% + N-methylpyrrolidone 50%]
[0046] 1. Use citric acid instead of oleic acid as a composite additive component;
[0047] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0048] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0049] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode;
[0050] Example 4: Composite additive [hexamethylcyclotrisiloxane 20% + oleic acid 20% + fatty acid polyoxyethylene ester 10% + N-methylpyrrolidone 50%]
[0051] 1. Use fatty acid polyoxyethylene ester instead of polyoxyethylene alkylphenol ether as the composite additive component;
[0052] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0053] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0054] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode;
[0055] Comparative Example 1: No additives used
[0056] 1. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride = 97:2:1;
[0057] 2. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0058] 3. After homogenization, apply and dry the slurry, and observe the appearance of the electrode;
[0059] Comparative Example 2: Composite additive [oleic acid 30% + polyoxyethylene alkylphenol ether 15% + N-methylpyrrolidone 55%]
[0060] 1. Eliminate the addition of hexamethylcyclotrisiloxane and prepare composite additives;
[0061] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0062] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0063] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode;
[0064] Comparative Example 3: Composite additive [30% hexamethylcyclotrisiloxane + 30% polyoxyethylene alkylphenol ether + 40% N-methylpyrrolidone]
[0065] 1. Eliminate the addition of oleic acid and prepare composite additives;
[0066] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0067] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0068] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode;
[0069] Comparative Example 4: Composite additive [hexamethylcyclotrisiloxane 30% + oleic acid 30% + N-methylpyrrolidone 40%]
[0070] 1. Eliminate the addition of polyoxyethylene alkylphenol ether and prepare composite additives;
[0071] 2. Mix the materials according to the ratio of active material: conductive carbon: polyvinylidene fluoride: composite additive = 97:2:0.8:0.2;
[0072] 3. Use a stirring device inside the laboratory to homogenize for 10 minutes;
[0073] 4. After homogenization, apply and dry the slurry, and observe the appearance of the electrode.
[0074] Coating effect analysis:
[0075] See Figure 1In implementation 1, the composite additive used is the optimal ratio of the patent of the present invention. Under the condition of high active substance ratio and low binder ratio, after homogenization coating, the surface of the pole piece is smooth and free of particles, which can meet the technical requirements; in implementation 2, hexamethylcyclotrisiloxane is replaced by octamethylcyclotetrasiloxane in the composite additive formula used. Under the condition of high active substance ratio and low binder ratio, after homogenization coating, the surface of the pole piece is smooth and free of particles, which can meet the technical requirements; in embodiment 3, oleic acid is replaced by citric acid in the composite additive formula used. Under the condition of high active substance ratio and low binder ratio, after homogenization coating, the surface of the pole piece is smooth and free of particles, which can meet the technical requirements; in embodiment 4, oleic acid is replaced by citric acid in the composite additive formula used. Under the condition of high active substance ratio and low binder ratio, after homogenization coating, the surface of the pole piece is smooth and free of particles, which can meet the technical requirements;
[0076] See Figure 2 In Comparative Example 1, homogenization was performed without adding a composite additive, and the homogenization time was consistent with the time when the composite additive was used. Particles existed on the surface of the electrode after coating, indicating that the composite additive of the present invention can improve the homogenization efficiency and shorten the homogenization time; in Comparative Example 2, the addition of hexamethylcyclotrisiloxane was eliminated from the composite additive used. Under the condition of high active substance ratio and low binder ratio, after homogenization coating, cracking and foil peeling occurred on the electrode during the drying process; in Comparative Example 3, the addition of oleic acid was eliminated from the composite additive used. Under the condition of high active substance ratio and low binder ratio, particles existed on the surface of the electrode after coating, causing electrode defects; in Comparative Example 4, the addition of polyoxyethylene alkylphenol ether was eliminated from the composite additive used. Under the condition of high active substance ratio and low binder ratio, particles existed on the surface of the electrode after coating, causing electrode defects.
[0077] Slurry stability analysis:
[0078] See Figure 3 In Examples 1-4, the relative backscattered light intensity of the slurry after standing for 24 hours was compared with that of the initial state. It can be seen that the light intensity of the slurry did not change significantly, indicating that the slurry has good stability;
[0079] See Figure 4 In comparative examples 1-4, the relative backscattered light intensity of the slurry after standing for 24 hours was compared with that in the initial state. It can be seen that the backscattered light intensity at the bottom of the slurry increased, and the slurry settled; at the same time, the backscattered light intensity in the middle decreased, and particles agglomerated in the middle of the slurry, indicating that the slurry has poor stability.
[0080] The present invention improves the interface wetting between the positive electrode material and the solvent, inhibits particle agglomeration, shortens the homogenization time, and improves production capacity; at the same time, it can improve the bonding performance of the slurry, enhance the peeling strength between the slurry and the current collector, and avoid the occurrence of pole piece defects; it is also suitable for other positive electrode materials such as lithium cobalt oxide and ternary materials, and can prevent the gel phenomenon of the positive electrode slurry.
[0081] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
Claims
1. A composite additive for lithium battery positive electrode slurry, characterized in that: The invention comprises the following raw materials in mass fractions: 15%-30% hexamethylcyclotrisiloxane, 15%-30% oleic acid, 5%-15% polyoxyethylene alkylphenol ether and 25%-65% N-methylpyrrolidone.
2. The method for using a composite additive for lithium battery positive electrode slurry according to claim 1, characterized in that: The steps include: Active material: conductive carbon: polyvinylidene fluoride: composite additive are mixed in a ratio of 97:2:0.8:0.2; the mixture is stirred into a slurry using a stirring device, and then coated.
3. The method for using a composite additive for lithium battery positive electrode slurry according to claim 2, characterized in that: The active material is lithium iron phosphate.
4. A composite additive for positive electrode slurry of lithium battery according to claim 1, characterized in that: The invention comprises the following raw materials in mass fractions: 20% hexamethylcyclotrisiloxane, 20% oleic acid, 10% polyoxyethylene alkylphenol ether and 50% N-methylpyrrolidone.
5. A composite additive for positive electrode slurry of lithium battery according to claim 2, characterized in that: The stirring device comprises a tank body (1) provided with an inlet pipe and an outlet pipe, a cover plate (2) being provided at the upper end of the tank body (1), a motor (3) being installed above the cover plate (2), a stirring assembly (4) and a material mixing assembly (5) being provided below the cover plate (2), and the motor (3) driving the stirring assembly (4) and the material mixing assembly (5) to reciprocate to stir and homogenize the mixture.
6. A composite additive for positive electrode slurry of lithium battery according to claim 5, characterized in that: The stirring assembly (4) comprises a rotating shaft (6) connected to the output shaft of the motor (3), a connecting piece (7) is externally connected to the rotating shaft (6), and stirring plates (8) are installed on both sides of the connecting piece (7).
7. A composite additive for positive electrode slurry of lithium battery according to claim 6, characterized in that: The material leveling assembly (5) comprises a gear (9) sleeved on the outside of the rotating shaft (6) and two symmetrically arranged racks (10), the gear (9) meshing with the racks (10), a connecting rod (11) is installed on the outside of the racks (10), a material leveling plate (12) is provided at the lower end of the connecting rod (11), a through hole (13) is opened on the material leveling plate (12), the rack (10) slides in two symmetrically structured limit blocks (14), and the limit blocks (14) are fixedly connected to the lower end of the cover plate (2).
Citation Information
Cited By
Preparation and coating method of lithium ion battery pole piece coating slurry
CN120895600A